Efeito do volume de calda na aplicação aérea de um regulador de crescimento no algodoeiro - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The main objective of the application of phytosanitary products is the efficient control of the biological target, be it insects, pathogens or weeds. The volume of the syrup and the type of the tip to be adopted can interfere in the form and amount of product that reaches the plant by changing the leaf cover or creating differentiated characteristics for the penetration of the drops in the target. The objective of this work was to evaluate the effect of the volume of syrup on the aerial application of the growth regulator at different stages of development of the cotton crop in the deposition and spectrum of drops at different spray tips. For this, two experiments were carried out, the first one evaluated four applications in cotton at 40, 60, 80 and 100 days after emergence, using the micronair atomizer, model AU-5000 LD, at the flow rates of 9, 12, 15, and 18 L ha-1, the second experiment used a hydraulic tip of the empty 45-cone conical jet model, with the same volumes of syrup and stages of development of the culture with aerial application. In the two experiments, a randomized complete block design was used in the 4 x 4 subdivided plots scheme, each experiment was composed of 16 treatments with four replications per treatment. The experiments were carried out in a commercial farm located in the municipality of Nova Xavantina - MT. The spraying spray deposition, the spectrum of drops in upper, middle and soil thirds between planting lines, percentage of interlining, leaf area, leaf area index, plant height, leaf diameter and leaf area were evaluated. the number of leaves, dry shoot mass, average number of beet per plant, droplet spectrum and spray deposition in the upper, middle and upper thirds for the applications of the regulator, and The purpose of this study was to verify the productivity of the cotton crop. The results showed that the different stages of development were responsible for the deposition of spray in the lower third of the canopy, in the droplet spectrum, due to differences in the closing percentage of the lines, leaf area, height, LAI, height cotton, and there was no influence of the volume of syrup applied. The combined analysis (clustering) of the experiments showed that the rotary atomizer provided a higher DMV in relation to the hydraulic tip, and it was possible to conclude that the spray volume did not influence the agronomic characteristics of the crop.
Effect of spray volume on aerial application of a growth regulator in cotton
Keywords: Aeronave agrícola; Estágios de desenvolvimento - Cultura do algodão; Gossypium hirsutum L.; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA AGRICOLA::MAQUINAS E IMPLEMENTOS AGRICOLAS